Change in prevalence of preterm birth in Israel following publication of national guidelines recommending routine sonographic cervical‐length measurement at 19–25 weeks' gestation. (7th April 2023) - Maymon, R.; Pekar‐Zlotin, M.; Meiri, H.; Haklai, Z.; Gordon, E.‐S.; Shlichkov, G.; Cuckle, H.
ABSTRACT: Objective: To compare the prevalence of preterm birth (PTB) (delivery before 37 weeks) in Israel before and after publication of national guidelines recommending second‐trimester sonographic cervical‐length (CL) measurement. Methods: The Israeli Society of Obstetrics and Gynecology (ISOG) guidelines, issued on 1 January 2012, specified that CL should be measured transabdominally or, if this is not possible, transvaginally, at the 19–25‐week ultrasound anomaly scan and that CL < 25 mm should indicate further work‐up and treatment, although the type of treatment was unspecified. In 2000, the Israel Ministry of Health issued a legal requirement for the submission of delivery records to a national registry. These data were used to compare PTB prevalence in the period before (2000–2011) and that after (2012–2020) publication of the guidelines, as well as trends within each time period. Information was available on singleton and multiple pregnancy and maternal age and parity, as well as low birth weight (< 2500 g). Results: During the period 2000–2020, there were 3 403 976 infants liveborn in Israel: 1 797 657 before and 1 606 319 after publication of the ISOG guidelines. There were 247 187 PTBs overall, with a prevalence of 7.64% (95% CI, 7.52–7.77%) before publication of the guidelines and 6.84% (95% CI, 6.43–7.24%) afterwards ( P < 0.0002, two‐tailed). The annual PTB prevalence was static in the first time period but declined by 0.18% per annum during the second period, after publication of the guidelines. The proportionate reduction in PTB prevalence after compared with before publication of the guidelines was 10% overall, 9% for PTB at 33–36 weeks, 18% for PTB at 28–32 weeks and 24% for PTB at < 28 weeks. After publication of the guidelines, reduced prevalence of PTB was observed among singletons (5.49% before vs 4.83% after, P < 0.0001), but not among infants in twin or higher‐order multiple pregnancy. There was a statistically significant reduction in the rate of PTB following publication of the guidelines in both nulliparous and parous women and in the 19–39‐year‐old maternal‐age group. Although reductions in PTB prevalence were also noted in high‐risk age groups (maternal age < 19 years and ≥ 40 years), these did not reach statistical significance. Following publication of the guidelines, there was a statistically significant reduction in the prevalence of birth weight under 2500 g, of a magnitude similar to that for PTB prevalence. Conclusions: The publication of national guidelines recommending routine CL measurement at the time of the second‐trimester anomaly scan was associated with a fall in PTB prevalence in singleton pregnancies. Whilst direct evidence linking screening with this fall in prevalence is lacking, it is likely that implementation of routine CL screening played an important role in the reduction of PTB rate. Our experience indicates that screening can be incorporated into the second‐trimester anomaly scan. © 2022 International Society of Ultrasound in Obstetrics and Gynecology.